Filsafat pendidikan Islam multikultural KH. Abdurrohman Wahid dan implementasinya dalam pendidikan Islam Indonesia - Lutfiana, Ulfa; Mispani, Mispani; Jaenullah, Jaenullah; Thohir, Muhyidin (Kuras Institute, 2023)
It is alleged that cultural pluralism in Indonesia still causes various problems such as racism, negative stereotypes, ethnocentrism, radicalism and environmental destruction. Seeing this phenomenon, KH. Abdurrohman Wahid looked for a solution by formulating an Islamic Education Philosophy with a multicultural pattern. This article aims to describe the Islamic Education Philosophy formulated by Abdurrohman Wahid and its implementation in Indonesia. The method used is a type of qualitative research using literature study. Data collection was carried out using the note-taking technique through related scientific references. Data analysis uses descriptive-analytic analysis. The results of this research show that the concept of Multicultural Islamic education from KH's perspective. Abdurrohman Wahid includes: First, the objectives of Multicultural Islamic education, namely; Islamic education based on neomodernism, Islamic education based on liberation, Islamic education based on multiculturalism. Second, the multicultural Islamic education curriculum prioritizes affective and psychomotor aspects, develops student-oriented patterns, educators are able to understand the meaning of education, create students who have an interest in learning, process-oriented patterns, and are vocationally based. The implementation of multicultural education can be implemented through various strategies in the form of cultural strategies, socio-political strategies, socio-cultural strategies, pedagogical strategies.